ANALISIS PEMILIHAN MODA TRANSPORTASI UMUM PADA LINTAS SURAKARTA-WONOGIRI - Hidayati, Lydia Novitriana Nur; Marcelino, Sanga Nico; Mahmudah, Amirotul Musthofiah Hidayah (Jurnal Teknik Sipil dan Arsitektur, 2026)
Public transportation plays a vital role in supporting mobility between Surakarta and Wonogiri, with Transjateng Bus and Batara Kresna Train as the main modes of transportation, which differ in terms of cost, travel time, and frequency of departure. This study analyses the factors influencing mode choice and compares revealed preferences and stated preferences through a survey of 126 respondents and a binomial logit model with variables including travel cost, travel time, and departure frequency. The results indicate that departure frequency is the most significant factor, particularly for the Batara Kresna Train. The stated preference scenario was designed with 12 attribute combinations using an orthogonal design, enabling simulation of service changes. The results indicate that departure frequency is the most significant variable influencing mode choice, particularly for trains. Under actual conditions (revealed preference), the Transjateng Bus is more dominant with a probability of 51.06%, while the Batara Kresna Train is only 48.94%. However, in the scenario of improved services for the Batara Kresna Train (stated preference), the probability of selection increases substaintially to 78.82%, highlighting the significant potential for improving train services to attract users. These findings can serve as an important reference for the Central Java Provincial Transportation Department and public transport operators in formulating transportation policies.